Certain victory the U.S. Army in the Gulf War - Scales, Robert H. 1944- (AUSA Institute of Land Warfare book., 1997)
Provides a picture of the US Army's performance during the Gulf War. It begins by chronicling the Army's regeneration in the two decades after Vietnam - the foundation of the Desert Storm victory. Each chapter starts with a personal combat story that puts the conflict into a human perspective.